2019
DOI: 10.21577/0103-5053.20190018
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Phenolic Compounds in Red Sweet Pepper (Capsicum annuum L.) using a Modified QuEChERS Method and UHPLC-MS/MS Analysis and Its Relation to Antioxidant Activity

Abstract: In the present work, a fast, easy and efficient analytical method was developed and validated for the determination of phenolic compounds (4-hydroxybenzoic, vanillic, caffeic, p-coumaric, sinapic, ferulic and ellagic acids, and naringenin) in red sweet pepper. Extraction of phenolic compounds was carried out using the quick, easy, cheap, effective, rugged and safe (QuEChERS) method, followed by separation and detection using ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 57 publications
1
21
3
1
Order By: Relevance
“…showed some changes compared to results of reports carried out by Blanco-Ríos et al (2013) and Rodrigues et al (2019). However, the differences between cultivars can be significantly affected by environmental factors (Hornero-Méndez et al 2000).…”
Section: The Phenolic Compounds Of Three Different Pepper Typescontrasting
confidence: 61%
“…showed some changes compared to results of reports carried out by Blanco-Ríos et al (2013) and Rodrigues et al (2019). However, the differences between cultivars can be significantly affected by environmental factors (Hornero-Méndez et al 2000).…”
Section: The Phenolic Compounds Of Three Different Pepper Typescontrasting
confidence: 61%
“…Some of the most prominent non-capsaicinoid phenolic compounds because of their valuable health benefits are phenolic acids like gallic acid, caffeic acid, chlorogenic acid or ellagic acid (Figure 2). Flavones are another important group of phenolic compounds, being some of the most prominent kaempferol, quercetin, luteolin or rutin (Figure 3) [26]. These phenolics have demonstrated great health benefits and many of them are commercially available in purified products extracted from other plant species [39,40].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…These phenolics have demonstrated great health benefits and many of them are commercially available in purified products extracted from other plant species [39,40]. Even so, their concentration differs among species but not much among varieties [26]. Other phenolic compounds are reviewed in the next paragraphs as in the case of some carotenoids or vitamins.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…In general, peppers have a significant contribution to human nutrition due to its carotenes, polyphenols, antioxidant properties, fatty acids (including palmitic (16:0), oleic (18:1n-9), and linoleic (18:2n-6) acids), vitamins (C and E) and mineral substances. The main phenolics compounds found in peppers pulp are ferulic acid (404-2661 µg/kg of fresh weight (fw)), ellagic acid (896–2434 µg/kg fw), synaptic acid (181–2025 µg/kg fw), naringenin (73–968 µg/kg fw), vanillic acid (45–149 µg/kg fw), caffeic acid (38–63 µg/kg fw), 4-hydroxybenzoic acid (18–37 µg/kg fw), and p-coumaric acid (14–69 µg/kg fw) [ 24 ]. Other studies show that most flavonoids found in peppers are aglycones and glycosides of myricetin, quercetin, luteolin, apigenin, and kaempferol [ 23 ].…”
Section: Main Raw Materials Used In Vegetable Soups and Cream Prodmentioning
confidence: 99%